STUDI KOMPARASI INTENSI KEWIRAUSAHAAN SISWA KETURUNAN ETNIS TIONGHOA DAN JAWA DI SMKS PANCA BHAKTI - Della Yunanda; Sri Buwono; Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine whether or not there is a difference in entrepreneurial intentions between Chinese and Javanese ethnic students at SMK Panca Bhakti Sungai Raya. This research is a quantitative study with a comparative method. The data sources in this study were 83 students consisting of 44 Chinese ethnic students and 39 Javanese ethnic students. The data were obtained using indirect communication techniques, namely by means of a questionnaire and documentation. The results of the descriptive analysis show that the entrepreneurial intention of Chinese ethnic students is in the very high category with a percentage of 83.72% and the entrepreneurial intention of Javanese ethnic students is in the very high category with a percentage of 82.44%. Then based on data analysis using the t test Independent Test through SPSS 23, the value of tcount 0.05) is obtained, so Ho (null hypothesis) is accepted and Ha (alternative hypothesis) is rejected. Thus it can be concluded that there is no significant difference in entrepreneurial intentions between ethnic Chinese and Javanese students at SMK Panca Bhakti Sungai Raya.Keywords: Chinese Ethnic, Entrepreneurial intention, Javanese Ethnic